2015
DOI: 10.3892/ol.2015.3466
|View full text |Cite
|
Sign up to set email alerts
|

Bak Foong pills combined with metformin in the treatment of a polycystic ovarian syndrome rat model

Abstract: Abstract. The aim of the present study was to investigate the treatment effects and associated mechanism of Bak Foong pills (BFPs) combined with metformin in the treatment of polycystic ovarian syndrome (PCOS). BFPs and/or metformin were administrated to treat the PCOS rats, and the weights and morphologies of the ovary, uterus and adrenal gland were measured. The levels of fasting blood glucose (FBG), serum testosterone (T), luteinizing hormone, fasting insulin (FIN) and insulin-like growth factor-1 were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
(31 reference statements)
2
10
0
Order By: Relevance
“…Ovary weight in postnatal DHEA‐treated rats was increased relative to that in controls; this was accompanied by ovarian cyst expansion, an increased number of cystic follicles, granular cell layer thinning, and thickening of the theca cell layer . DHEA‐treated mice showed normal ovary weight and growing follicle and CL populations …”
Section: Androgen‐induced Pcos Modelsmentioning
confidence: 97%
See 2 more Smart Citations
“…Ovary weight in postnatal DHEA‐treated rats was increased relative to that in controls; this was accompanied by ovarian cyst expansion, an increased number of cystic follicles, granular cell layer thinning, and thickening of the theca cell layer . DHEA‐treated mice showed normal ovary weight and growing follicle and CL populations …”
Section: Androgen‐induced Pcos Modelsmentioning
confidence: 97%
“…Women with PCOS have high levels of DHEA; therefore, DHEA is administered to rodents to generate PCOS models. A typical protocol is 6 mg/100 g body weight/day starting from postnatal day 21 to 23 for about 20‐40 consecutive days . DHEA has been administered by implantation of 7.5‐mg 90‐day continuous‐release pellets in mouse models …”
Section: Androgen‐induced Pcos Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu Ji Bai Feng Pill (WJBFP) is a well‐known TCM formula that has been widely prescribed in clinical practice in China and other Asian countries, composed of 14 plant and six animal crude materials, namely, Angelicae Sinensis Radix, Chuanxiong Rhizoma, Paeoniae Radix Alba, Rehmanniae Radix, Rehmanniae Radix Praeparata, Salviae Miltiorrhizae Radix et Rhizoma, Glycyrrhizae Radix et Rhizoma, Astragali Radix, Ginseng Radix et Rhizoma, Cyperi Rhizoma, Dioscoreae Rhizoma, Asparagi Radix, Stellariae Radix, Euryales Semen, Gallus Domesticus (black bone chicken), Cervi Cornus Colla, Cervi Cornu Degelatinatum, Ostreae Concha, Trionycis Carapax, and Mantidis Oötheca . According to TCM theories, WJBFP possesses beneficial effects of warm reinforcing, nourishing yin , resolving blood stasis, and harmonizing the body to treat gynecological disorders such as dysmenorrhea, amenorrhea, and infertility for hundreds of years . Modern pharmacological studies have demonstrated that WJBFP was reasonably combined, and was recognized as a prescription for tonifying the kidney, ovary, and uterus from a whole aspect, thus reducing the androgen level, promoting the follicular development, as well as improving the ovulation disorders .…”
Section: Introductionmentioning
confidence: 99%
“…According to TCM theories, WJBFP possesses beneficial effects of warm reinforcing, nourishing yin , resolving blood stasis, and harmonizing the body to treat gynecological disorders such as dysmenorrhea, amenorrhea, and infertility for hundreds of years . Modern pharmacological studies have demonstrated that WJBFP was reasonably combined, and was recognized as a prescription for tonifying the kidney, ovary, and uterus from a whole aspect, thus reducing the androgen level, promoting the follicular development, as well as improving the ovulation disorders . Therefore, it is necessary to analyze the chemical constituents in WJBFP to interpret its pharmacological material basis.…”
Section: Introductionmentioning
confidence: 99%